Best Proximity Point for Generalized and S-Geraphty Contractions - Abdelhafid Bassou; Taoufik Sabar; Mohamed Aamri (Abstract and Applied Analysis)
This paper introduces a new class of mappings called S-Geraphty-contractions and provides sufficient conditions for the existence and uniqueness of a best proximity point for such mappings. It also presents the best proximity point result for generalized contractions as well. Our results extend and generalize some theorems in the literature.